Chinese milk vetch incorporation inhibits nitrification by suppressing comammox Nitrospira in subtropical paddy soils - Mengmeng Feng; Yongxin Lin; Jia Liu; Xiangyin Ni; Yuheng Cheng; Hang-Wei Hu; Juntao Wang; Luyuan Sun; Zi-Yang He; Ji-Zheng He (Geoderma, 2025)
Chinese milk vetch (Astragalus sinicus L.) incorporation (CVI), straw return (SR), and nitrogen reduction (NR) are common agricultural practices, but their impacts on soil nitrogen (N) cycling processes and associated microbial communities remain poorly understood. In this study, CVI, SR, and NR effects on soil net N mineralization and potential nitrification rates, the abundance/activity of ammonia oxidizers, and comammox Nitrospira (COMX) community structure were examined. While CVI significantly increased the net N mineralization rate and acid-hydrolysable N fraction, SR and NR did not affect these values. At the same time, CVI decreased the potential nitrification rate and reduced COMX clade A amoA gene and transcript copy number, whereas SR and NR increased amoA gene copy number. DNA stable isotope probing (DNA-SIP) revealed that COMX clade A played a critical role in nitrification. COMX community richness was reduced by CVI and increased by SR. COMX community structure was also shaped by CVI, with soil NH4+-N and pH acting as two key moderators of these effects. Additionally, CVI increased the influence of deterministic processes on COMX community assembly. Together, these findings indicate that CVI enhances N mineralization while simultaneously reducing nitrification, potentially improving N retention. These results enhance our mechanistic understanding of N cycling, allowing for the optimization of fertilization strategies to balance agronomic productivity with environmental sustainability.